2011
DOI: 10.1080/15459624.2011.559417
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Diagnostic Computer-Based Air and Forehead Bone Conduction Audiometry

Abstract: Computer-based audiometry allows for novel applications, including remote testing and automation, that may improve the accessibility and efficiency of hearing assessment in various clinical and occupational health settings. This study describes the validity of computer-based, diagnostic air and forehead bone conduction audiometry when compared wtih conventional industry standard audiometry in a sound booth environment. A sample of 30 subjects (19 to 77 years of age) was assessed with computer-based (KUDUwave 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 11 publications
11
52
2
Order By: Relevance
“…Air-conduction thresholds measured in the natural and standard audiometric booth corresponded within typical 5dB or less test-retest limits for thresholds measured in a sound booth (Stuart et al 1991;Smith-Olinde et al 2006;Margolis et al 2010;Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011). Average absolute air-conduction threshold differences for the current study (2.7 ± 3.1 dB) were within previously reported average test-retest absolute difference values (3.6 ± 3.9 dB and 3.5 ± 3.8 dB) for the same audiometer (Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Air-conduction thresholds measured in the natural and standard audiometric booth corresponded within typical 5dB or less test-retest limits for thresholds measured in a sound booth (Stuart et al 1991;Smith-Olinde et al 2006;Margolis et al 2010;Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011). Average absolute air-conduction threshold differences for the current study (2.7 ± 3.1 dB) were within previously reported average test-retest absolute difference values (3.6 ± 3.9 dB and 3.5 ± 3.8 dB) for the same audiometer (Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Placement of the insert earphones was deep with the foam tip inserted completely into the canal to improve the attenuation of ambient noise (Berger & Killion, 1989;Berger, 1983;Berger, Kieper & Gauger 2003) and to minimize the occlusion effect. Placing insert earphones down to the bony part of the ear canal reduces the occlusion effect allowing for bone-conduction evaluation with occluded ears (Dean & Martin, 2000;Stenfelt & Goode, 2005;Swanepoel & Biagio, 2011). Deep insertion required removal of cerumen by the audiologist in 24.5% of the subjects prior to their inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean ambient noise level when there was no outpatient clinic in progress was measured at 46 dBA. Placing insert earphones down to the bony part of the ear canal also reduces the occlusion effect allowing for bone-conduction evaluation with occluded ears using insert earphones (Slevin et al, 2000;Swanepoel & Biagio, 2011). However, not removing the insert earphone is a limitation to the technique as insertion down to the bony portion of the ear canal cannot be confirmed or guaranteed.…”
Section: Index Test: Automated Audiometrymentioning
confidence: 99%
“…The ability to provide automated audiometric testing in the absence of a sound-treated environment has a great potential to increase service provision to low and middle-income countries, and rural and remote areas of high-income countries that do not have these facilities. At least two of the contemporary clinically available automation-capable audiometers use audiocups to provide attenuation from environmental sounds (Margolis et al, 2010;Swanepoel & Biagio, 2011), and studies have demonstrated their potential feasibility in environments that are not soundtreated Maclennan-Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%